2018
DOI: 10.5792/ksrr.17.201
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Injection of Bone Marrow-Derived Mesenchymal Stem Cells Leading to Better Clinical Outcomes without Difference in MRI Outcomes from Baseline in Patients with Knee Osteoarthritis

Abstract: PurposeBone marrow (BM) is frequently used as a source of mesenchymal stem cells (MSCs) because they have a high potential for differentiation. However, it is unclear whether BM-derived MSCs lead to better clinical and magnetic resonance imaging (MRI) outcomes postoperatively.Materials and MethodsThis meta-analysis compared the clinical and MRI outcomes in patients with knee osteoarthritis (OA) treated with BM-derived MSCs. Eight studies comparing the clinical and MRI outcomes assessed with various measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 29 publications
0
40
0
1
Order By: Relevance
“…[158][159][160] Clinical trials of intra-articular injection of MSCs into the knee with OA have exhibited reliable safety and feasibility, 161,162 while this approach could ameliorate the knee society clinical rating system (KSS) and OA outcome score 163,164 and partially alleviate knee pain. [165][166][167][168] However, the detailed mechanisms for this and other stem cell-based OA treatments have not been well clarified. An increasing number of studies have suggested that the therapeutic effects of stem cells are mainly dependent on the paracrine function of stem cells, including the secretion of EVs.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…[158][159][160] Clinical trials of intra-articular injection of MSCs into the knee with OA have exhibited reliable safety and feasibility, 161,162 while this approach could ameliorate the knee society clinical rating system (KSS) and OA outcome score 163,164 and partially alleviate knee pain. [165][166][167][168] However, the detailed mechanisms for this and other stem cell-based OA treatments have not been well clarified. An increasing number of studies have suggested that the therapeutic effects of stem cells are mainly dependent on the paracrine function of stem cells, including the secretion of EVs.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…It has been demonstrated that gelMA supports cartilage-like matrix production when a suspension of single chondrocytes or mesenchymal stem cells (MSC) were embedded (Hu et al, 2009;Schuurman et al, 2013;Mouser et al, 2018;Pahoff et al, 2019). Recently, there has been an increased interest in the use of adult MSC in cartilage regeneration because of their multipotency and ability to differentiate into chondrogenic lineages after expansion in vitro and intra-articular injections of MSC have been performed to reduce osteoarthritic pain or induce cartilage repair (Jo et al, 2014;Shin et al, 2018). The use of MSC would also eliminate the need for harvesting surgery within the damaged knee-joint or donor site.…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of tendinosis seen in the supraspinatus, infraspinatus, and subscapularis remained unchanged at 12 months. Similar outcomes have been seen with individuals undergoing regenerative procedures in the past with improvement in pain and function without significant structural changes on diagnostic imaging [19][20][21]. Furthermore, studies have shown that structural changes seen on MRI that may be suggestive of pathology can be seen in both symptomatic and asymptomatic patients [22].…”
Section: Discussionmentioning
confidence: 55%